PhI(OAc)2 mediated radical trifluoromethylation of vinyl azides with Me3SiCF3 - Wang, Yi-Feng (2014)
The fluorine-containing organic motif is becoming privileged in pharmaceuticals, agrochemicals, and functional materials, owing to its unique properties such as electron-withdrawing character, metabolic stability, and lipophilicity. Described herein is the PhI(OAc)2-mediated radical trifluoromethylation of vinyl azides with Me3SiCF3 to efficiently generate α-trifluoromethyl azines. The resulting α-trifluoromethyl azines were successfully transformed to valuable fluorine-containing molecules such as α-trifluoromethyl ketones, β-trifluoromethyl amines, 5-fluoropyrazoles, and trifluoroethyl isoquinolines.